Manusia Mencari Makna dalam Pergulatan Kaum Eksistensialis - Purnama, Agustinus (Jurnal Orientasi Baru, 2010)
SÃ¸ren Kierkegaard triggered a movement of the existentialist philosophical schools. He brought back philosophy to the real meaning of human life. The true meaning does not depend on a speculative truth, but on the real life existence. Jean Paul Sartre put emphasis on the free choice to grasp a real meaning of life. One makes choice from some alternatives. Subsequently one has to be responsible of oneâ€™s choice. Sartreâ€™s philosophical idea and statements became favorite of his time. Gabriel Marcel wrote his philosophical reflection with his high appreciation to the human being as mystery. The relation between â€œI and thouâ€, even â€œI and Thouâ€ have given a different angle to Sartreâ€™s. What are the significance of the existentialist schools for our contemporary society?